Teaching Personnel’s Perception of Private Primary Schools’ Contribution to Educational Growth in Ijebu-North Local Government Area, Ogun State, Nigeria. - Oguntimehin, Abiodun; Oni, Joshua (NIU Journal of Social Sciences, 2017)
This study investigated the perception of teachers of private and public primary schools on the contribution of private primary schools to educational development in Ijebu-North Local Government Area, Ogun State.  A research question was drawn and two null hypotheses were formulated.  The descriptive survey research design was adopted for the study.  Twenty-four (24) approved private primary schools, having twenty-four (24) head teachers and three hundred and eighty-five (385) teachers; and one hundred and one (101) public primary schools with 101 head teachers and one thousand, one hundred (1,100) teachers made up the population.  The sample was selected using stratified random sampling technique.  It comprised twenty-four (24) (100%) approved private primary schools and their 24 (100%) head teachers and three hundred and ten (310) (i.e. 80.5%) teachers; as well as fifty (50) (i.e. 49.5%) public primary schools and their 45 (i.e. 44.6%) head teachers and five hundred and fifty (550) (i.e. 50%) teachers.  A questionnaire, entitled: ‘Private Primary Schools’ Contribution to Educational Development Questionnaire (PPSCEDQ)’ was used in collecting information.  The analysis of data revealed, among others, that private primary schools were contributing significantly to educational development in the local government area.  The performance could, however, be further enhanced if they are adequately monitored and supervised by the government. Keywords:       Educational development; Private primary schools